2020
DOI: 10.1186/s12913-020-05194-6
|View full text |Cite
|
Sign up to set email alerts
|

Rural and urban differences in health system performance among older Chinese adults: cross-sectional analysis of a national sample

Abstract: Background: Despite improvement in health outcomes over the past few decades, China still experiences striking rural-urban health inequalities. There is limited research on the rural-urban differences in health system performance in China. Method: We conducted a cross-sectional analysis to compare health system performance between rural and urban areas in five key domains of the health system: effectiveness, cost, access, patient-centredness and equity, using data from the WHO Study on Global AGEing and adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…More than half of the studies ( n = 12) reported income‐ or wealth‐related discrimination 6,8,13,14,16–18,21,22,24–26 . The majority of the studies were conducted in China except one in South Korea, 14 one in the USA, 18 and one in Italy, Spain, and Portugal 8 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More than half of the studies ( n = 12) reported income‐ or wealth‐related discrimination 6,8,13,14,16–18,21,22,24–26 . The majority of the studies were conducted in China except one in South Korea, 14 one in the USA, 18 and one in Italy, Spain, and Portugal 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Access to primary care also demonstrated a pro‐rich inequality 8 . Seven studies from China highlighted pro‐poor inequality in accessing elder care in health facilities 6,16,17,21,22,25,26 . Another study from China revealed a difference in health service utilization among the floating elderly population irrespective of insurance coverage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the overall hypertension management ability was higher for physicians in Mongolia than the rural physicians in our study, with their scores for the general knowledge, attitude, practice, priority, and confidence for hypertension management being 53.1%, 76.5%, 31.0%, 85.7%, and 63.2%, respectively. Studies have shown that patients in rural China experience poorer hypertension management than those in urban regions 11,12 . While several studies on hypertension management focus on physicians’ job satisfaction, 29 and the patients’ trust in them 30 ; few studies focus on the physicians’ management abilities.…”
Section: Discussionmentioning
confidence: 99%